Cadherin 17 is frequently expressed by 'sclerosing variant' pancreatic neuroendocrine tumour. Issue 2 (28th October 2014) - Johnson, Adam; Wright, Jesse P; Zhao, Zhiguo; Komaya, Tatsuki; Parikh, Alexander; Merchant, Nipun; Shi, Chanjuan
<x xml:space="preserve">Abstract</x> Aims Recently, we described a series of pancreatic neuroendocrine tumours (PanNETs) featuring prominent stromal fibrosis, which we called sclerosing PanNETs. The aim of this study was to examine the pathological, immunophenotypic and clinical differences between sclerosing and non‐sclerosing PanNETs. Methods and results One hundred and six PanNETs were identified, of which 15 (14%) were sclerosing NETs. Tissue microarrays containing 44 non‐sclerosing and five sclerosing PanNETs, as well as sections from 10 additional sclerosing tumours, were immunohistochemically labelled for serotonin, CDX2, CDH17, and islet 1. Sclerosing PanNETs were smaller (P = 0.045) and more likely to show an infiltrative growth pattern (P < 0.001) than non‐sclerosing PanNETs. They were frequently associated with a large pancreatic duct, causing duct stenosis. Additionally, we found significantly increased expression of the small intestinal NET markers serotonin, CDX2 and CDH17 in sclerosing PanNETs (P < 0.001) as compared with non‐sclerosing PanNETs. No difference in clinical outcome was found; however, more sclerosing PanNETs were stage IIB or above (P = 0.035), with lymph node metastasis being seen in three of nine sclerosing PanNETs with a tumour size of <20 mm. Conclusions Sclerosing PanNETs have distinct pathological features and biomarker expression profiles. In addition, lymph node metastasis can be present even with small sclerosing PanNETs.